Frontispiece: Synthesis and Two‐Dimensional Chiral Surface Self‐Assembly of a π‐Conjugated System with Three‐Fold Symmetry: Benzotri(7‐Azaindole). Issue 4 (18th January 2021) - Rodríguez, Luis M.; Gómez, Paula; Más‐Montoya, Miriam; Abad, José; Tárraga, Alberto; Cerdá, Jorge I.; Méndez, Javier; Curiel, David
Abstract : Self‐Assembly The rational design, synthesis, and two‐dimensional self‐assembly of benzotri(7‐azaindole) is reported by Javier Méndez, David Curiel et al. in their Research Article on page 1782 .